Meningkatkan Pengetahuan Masyarakat Desa Dukuh Tentang TPT Melalui Penyuluhan Kesehatan dan Pendidikan Kesehatan Berbasis Komunitas - Zita Atzmardina; Rosyikhotul Ma'rifah; Cindy Clarissa S; Irvan Baharits Al Basith (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. It is transmitted through the air, specifically through droplets expelled by sufferers when coughing or sneezing. TB is divided into two main types: pulmonary TB, which attacks the lungs, and extrapulmonary TB, which can affect other organs such as the pleura, lymph nodes, skin, bones, and meninges. In the Community Health Center (Puskesmas) work area, 77 new cases of pulmonary TB were recorded from January to April 2025. Meanwhile, coverage of Tuberculosis Prevention Therapy (TPT) only reached 44.7%, still below the national target of at least 50%. This condition indicates the need for increased health promotion activities and community diagnostic approaches as promotive and preventive measures, in order to increase TPT coverage and reduce the incidence of TB. The results of the respondent questionnaire showed that the level of public knowledge about TB reached 64.6%, positive attitudes at 94%, and preventive behavior at 72%. Based on these findings, it is recommended that outreach activities be conducted regularly to improve public understanding, which can ultimately encourage behavioral changes and reduce TB cases.